A synthetic sialic acid analog that is resistant to the receptor-destroying enzyme can be used by influenza C virus as a receptor determinant for infection of cells - Herrler, Georg; Groß, Hans Jürgen; Brossmer, Reinhard (Biochemical and biophysical research communications, 1995)
A synthetic sialic acid analog, N-acetyl-9-acetamido-9-deoxy-neuraminic acid, can be used by influenza C virus as a receptor determinant for attachment to cells, In contrast to the natural determinant, N-acetyl-9-O-acetylneuraminic acid, the synthetic sialic acid is resistant to the action of the receptor-destroying acetylesterase of this virus. The sialic acid analog was enzymatically transferred to the surface of Madin-Darby canine kidney cells that are resistant to infection because of a lack of receptors. Influenza C virus was able to infect the modified cells though requiring a 10-fold larger amount of the sialic acid analogue on the cell surface compared to the natural receptor determinant. The quantitative difference is accounted for mainly by a less efficient binding of influenza C virus to the analog. Thus, in our system, inactivation of the receptor by the viral esterase is not required for the initiation of an influenza C virus infection.